Kegiatan Ektrakurikuler Tilawah Untuk Meningkatkan Prestasi Peserta Didik di SD Istiqomah Bandung - Kinesti, Rakanita Dyah Ayu; Ixzata, Musabiqul Fikriansyah Al; Ni’mah, Rizqiya Afifatun; Munawaroh, Sani’atul; Ulya, Nadia Himatul; Agustin, Rani (Lembaga Yasin AlSys, 2022)
Improving the quality and quality of an educational institution in terms of various aspects, one of which is increasing achievement in extracurricular programs. SD Istiqomah Bandung is a large educational institution and has many proud achievements, especially in the recitation program. The general purpose of this study is (1) to find out the description of extracurricular activities that can improve learning outcomes at SD Istiqomah Bandung. (2) to find out the achievements of students at SD Istiqomah Bandung which are produced through recitation extracurricular activities. (3) To find out the results obtained after participating in extracurricular recitations at SD Istiqomah in class subjects. In this study using qualitative research methods in which the way of collecting data by question and answer, observation, and documentation. From this extracurricular recitation activity, it is hoped that students at Istiqomah Elementary School can encourage talents and interests so as to increase the achievements of students which later can also be applied or implemented in life in society. The conclusions of this study have a direct impact on school achievement which makes SD Istiqomah Bandung a superior elementary school in the city of Bandung.